Psychological capital appreciation as a mediator between resilience and burnout among ICU nurses - Zhang, Rui; Shan, Mei; Yin, Yanling; Wu, Yanshuo; Gao, Peng; Xin, Yan; Shen, Kangkang (Frontiers in Public Health, 2025)
ObjectiveThis study investigated the mediating effects of psychological capital appreciation in the relationship between psychological resilience and burnout among ICU nurses. The findings aim to provide an objective reference for hospitals to enhance the occupational health of ICU nurses.MethodsA cross-sectional questionnaire survey was administered to 150 ICU nurses employed at 20 tertiary hospitals across Hebei Province. Stratified random sampling was employed in the sampling methodology, with strata defined by hospital size and ranking. Subsequently, ICU nurses were randomly selected within each stratum to enhance the representativeness of the sample.Results(i) Among the 150 nurses, the psychological resilience score was (68.701 ± 14.549), resilience was (63.547 ± 14.020), and burnout score was (65.095 ± 18.461). (ii) The analysis revealed that psychological capital appreciation mediated the relationship between psychological resilience and burnout, with a mediation effect size of 0.597, accounting for 79% of the total effect. (iii) Psychological resilience did not directly affect job burnout (direct effect = 0.148, 95% CI includes 0, t = 0.864, p = 0.389), but indirectly reduced burnout by enhancing PCA. The indirect effect was significant (indirect effect = 0.601, 95% CI excludes 0, z = 6.073, p = 0.000), with a total effect size of 0.748 (95% CI excludes 0, z = 8.486, p = 0.000).Conclusion(i) Psychological capital appreciation (PCA) plays a complete mediating role between resilience and job burnout of ICU nurses. (ii) The overall incidence of job burnout among nurses is high, while the levels of resilience and psychological capital appreciation are at a low to medium level, which need to be improved urgently.